Penerapan Modul Ajar Berbasis Pendekatan Deep Learning untuk Meningkatkan Hasil Belajar IPAS Kelas 5 - Reni Rostika; Dina Apriana; Subandi; Dinda Nurizzati; Zurriatun Thoibah (Jurnal Pendidikan, Sains, Geologi, dan Geofisika (GeoScienceEd Journal), 2026)
This study was motivated by the low student achievement in the 5th-grade IPAS subject at SDN 2 Sandubaya. The purpose of this study was to improve student achievement through the implementation of a teaching module based on the deep learning approach. This study was a Classroom Action Research (CAR) project conducted in three cycles, with each cycle consisting of four stages: planning, implementation, observation, and reflection. The research subjects were 25 fifth-grade students. Data were collected through achievement tests, observations, and documentation. The results showed that student achievement improved in each cycle. In Cycle I, the achievement rate reached 64%, increased to 72% in Cycle II, and rose further to 88% in Cycle III, exceeding the established success indicators. Thus, it can be concluded that the implementation of a deep learning-based instructional module is effective in improving the IPAS learning outcomes of fifth-grade students. This effectiveness stems from the fact that the deep learning approach fosters students’ understanding in a mindful, meaningful, and joyful learning.